AI in the Classroom: A rapid evaluation of AI-generated lesson plans in Islamabad’s public schools - Aslam, Nawaz; Qureshi, Ghada; Hassan, Syed Mustafa (EdTech Hub, 2025)
This report presents a rapid evaluation of AI-generated lesson plans currently being used in public schools in rural and urban Islamabad under the National Institute of Excellence in Teacher Education (NIETE). These centrally developed, scripted lesson plans are aligned with the national curriculum and built on the Gradual Release of Responsibility (GRR) model, with additional elements of the 5E and Inquiry-Based Learning (IBL) models in science, and the Concrete-Pictorial-Abstract (CPA) model in maths. Using a mixed-methods approach—including teacher surveys, focus group discussions, key informant interviews, and an expert rubric-based review—the study assesses the lesson plans' quality, relevance, and adaptability. Teachers expressed strong support for the lesson plans, especially in terms of reduced workload and structured delivery, though concerns were raised around flexibility, contextual responsiveness, and teacher agency. While the study does not evaluate student learning outcomes, it provides actionable insights and recommendations for improving the design, support, and implementation of AI-generated instructional tools, particularly as the programme scales to other provinces in Pakistan, such as Balochistan. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Usawa na maamuzi katika Mafunzo Endelevu ya Walimu Kazini yanayowezeshwa na Teknolojia nchini Tanzania: Zana za utafiti - Chachage, Kristeen; Swai, Calvin; Rwambali, Innocent; Hennessy, Sara; Koomar, Saalim; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Mwakabungu, Fika; et al. (EdTech Hub, 2025)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Chuo Kikuu cha Dodoma, Chuo Kikuu cha Aga Khan, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza upanuzi na mabadiliko ya kuendana na mahitaji ya walimu na mazingira ya shule katika utekelezaji wa Mafunzo Endelevu ya Walimu Kazini (MEWAKA) unaojumuisha matumizi ya teknolojia. Katika kuandaa zana hizi, tumetumia zana zilizochapishwa katika awamu ya kwanza ya utafiti huu na mifano kutoka sehemu mbalimbali, kwa kuzingatia mifano mizuri ya utafiti kuhusu elimu. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Equity and Agency in Technology-Supported Teacher Professional Development in Tanzania: Research Instruments Pack - Chachage, Kristeen; Hennessy, Sara; Koomar, Saalim; Swai, Calvin; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Mwakabungu, Fika; Mrosso, Vicky; et al. (EdTech Hub, 2025)
This pack contains links to research instruments developed by EdTech Hub, the University of Dodoma, Aga Khan University, and Tanzania Institute of Education for the second phase of a study investigating the scale-up and local contextualisation of a national technology-supported teacher professional development programme known as MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, which translates as ‘teacher continuous professional development’ [TCPD] in English). The instruments draw on previously published research instruments used in Phase 1 of our research, plus examples from other sources that exemplify best practices in education research. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Enquête nationale sur la possession et les usages des technologies parmi les enseignants du primaire - Rasolohery, Hasiniavo; Mitchell, Joel (EdTech Hub, 2025)
This document presents a report of a national survey on technology ownership and usage among primary school teachers in Madagascar, conducted in 2023. The survey, a collaboration between EdTech Hub, the National Institute of Pedagogical Training (INFP), and the Ministry of National Education, aimed to gather reliable data on ICT deployment across Madagascar's 23 regions. Data was collected through quantitative surveys and qualitative focus groups involving 1403 educators. Key findings reveal that while 97% of educators own technological tools, basic mobile phones are most prevalent. Smartphone ownership is significant, but usage is largely limited to calls and SMS, indicating underutilisation of advanced features. Internet access is limited, with only 25.2% of teachers accessing it via smartphone. Electricity access is relatively high at 89%, primarily through the national grid and solar energy. The report highlights the need for ICT training to enhance teachers' digital skills and recommends deploying offline systems to overcome connectivity issues. It also emphasises adapting content for teachers with disabilities and considering the predominantly regional language usage in professional settings. Keywords: national teacher survey; technology access; technology use; Madagascar; primary school Ce document présente un rapport sur une enquête nationale menée en 2023 sur la possession et l’usage des technologies par les enseignants du primaire à Madagascar. Cette enquête, réalisée en collaboration entre EdTech Hub, l’Institut National de Formation Pédagogique (INFP) et le Ministère de l’Éducation Nationale, visait à recueillir des données fiables sur le déploiement des TIC dans les 23 régions du pays. Les données ont été collectées à travers des enquêtes quantitatives et des groupes de discussion qualitatifs impliquant 1 403 enseignants. Les résultats clés révèlent que, bien que 97 % des enseignants possèdent des outils technologiques, les téléphones mobiles basiques sont les plus répandus. La possession de smartphones est significative, mais leur utilisation se limite principalement aux appels et aux SMS, ce qui indique une sous-utilisation des fonctionnalités avancées. L’accès à Internet reste limité, avec seulement 25,2 % des enseignants l’utilisant via un smartphone. L’accès à l’électricité est relativement élevé (89 %), principalement via le réseau national et l’énergie solaire. Le rapport souligne la nécessité d’une formation aux TIC pour améliorer les compétences numériques des enseignants et recommande le déploiement de systèmes hors ligne pour pallier les problèmes de connectivité. Il met également l’accent sur l’adaptation des contenus aux enseignants en situation de handicap et sur la prise en compte de l’usage majoritaire des langues régionales dans les environnements professionnels. Mots clés: enquête nationale des enseignants; accès à technologie; utilisation de technologie; Madagascar; Moodle; école primaire An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Demand-Driven Evidence Delivery and Uptake: Reflections on the Edtech Hub Helpdesk - Jordan, Katy; Thakrar, Jayshree; Patel, Prachi; Ramesh Vasudevan, Sharanya; Coflan, Caitlin; Thang, Sarah; Myers, Christina (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

TCPD in Tanzania: Design-Based Implementation Research Cycle 2 Recommendations - Chachage, Kristeen; Koomar, Saalim; Swai, Calvin; Massam, Winston; Hennessy, Sara; Masonda, Jonathan Paskali; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Frederick; Komba, Aneth; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the second cycle of the DBIR carried out between September and November 2023. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; Tanzania; communities of learningAn output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech Horizon Scan: Rapid scan on emerging EdTech research during the Covid-19 pandemic. - Ampofo, Rudolph; Kaye, Tom (EdTech Hub, 2022)
EdTech Hub horizon scans are publications designed to provoke thinking and provide insight into a range of topics related to the design, implementation, oversight, and monitoring and evaluation of educational technology (EdTech) tools, products, services, and related ideas. This edition of the Hub’s Horizon Scan provides a high-level summary of research, blogs, and think-pieces published between October and December 2021, that provide insights and learnings on the adoption and utilisation of EdTech during the Covid-19 pandemic. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen